Wave of Hope Retrospective : Thailand Capacity-Building After the Asian Tsunami in the Indian Ocean - Woodworth, Warner (Archives of Business Research, 2021)
This research reports and analyzes the launch of a small Non-Governmental Organization (NGO) called Wave of Hope to assist in helping Thai villagers along coastal areas to confront tragedy and death from the 2004 tsunami. The terrible destruction of mass flooding is reported and the subsequent design and launch of this little effort is described. A report on the social and economic changes that emerged over the years that followed is made. Finally, the promising potential of university students to use their course learning with real-world applications is summarized and a call to action for further outreach responses to future disasters is articulated.